MHC class II distribution in dendritic cells and B cells is determined by ubiquitin chain length - Ma, Jessica K. (National Academy of Sciences, 2012)
Dendritic cells (DCs) and B cells present antigen-derived peptides bound to MHC class II (MHC II) molecules for recognition by CD4-positive T lymphocytes. DCs control the intracellular traffic of peptide–MHC II complexes by regulating the ubiquitination of MHC II. In resting or “immature” DCs, ubiquitinated MHC II molecules are targeted to lysosomes, but upon pathogen-induced “maturation,” ubiquitination is down-regulated and MHC II can accumulate on the plasma membrane of mature DCs. Although B cells constitutively ubiquitinate their MHC II, it unexpectedly remains at the surface. We find that DCs and B cells differ in MHC II-conjugated ubiquitin (Ub) chain length: four to six Ub in immature DCs vs. two to three in B cells. In both cell types, experimentally increasing Ub chain length led to efficient lysosomal transport of MHC II, whereas MHC II with fewer than two Ubs did not reach lysosomes. Thus, Ub chain length plays a crucial role in regulating the intracellular fate and function of MHC II in DCs and B cells.